The effect of financial integration on financial development: Evidence from ASEAN countries - Syarifah Intan Munirah, Sayed Mahadzir (2017)
Under the International Monetary Fund and World Bank structural adjustment reform programs, integration was introduced to the developing countries as a means of growing these economies. The objective of the study is to determine the effect of financial integration on financial development for nine major economies in ASEAN countries. This study employs the unbalanced panel data for nine selected ASEAN countries, which are Malaysia, Indonesia, Thailand, Singapore, Cambodia, Myanmar, Philippines, Vietnam and Laos for the period 2004 and 2014. The study uses secondary data since the nature of the data is quantitative. It focused on six key variables namely financial depth as a dependent variable while financial integration, economic growth, inflation, real interest rate and income group as independent variables. The study discovers the positive relationship between financial integration and financial depth for nine ASEAN countries. In addition, the study also finds a positive link between economic growth and financial depth. The findings of this study will provide insights to regulators in improving rules and regulations of their country in order to reduce the restrictions of external account into the country.